Activating effect of Aromatherapy Inhalation with Citrus Hystrix (Kaffir Lime) leaves oil - Alisa Stephanie Rasion
Citrus hystrix leaves oil has a scent with unique nuances because it is rich in natural constituent citronellal which possesses soothing properties and has the potential to be used as aromatherapy. However, there have been relatively few published about the C. hystrix leaves extract and its efficacy as aromatherapy. This research was aimed to investigate the effects of C. hystrix leaves oil on human behavioural parameters after inhalation. C. hystrix essential oil was obtained from fresh leaves by steam distillation and the oil yield obtained was 0.14% with pale yellow in colour while the chemical profile of C. hystrix leaves volatile oil was analysed using the gas cromatography-mass spectrometry (GC-MS). It was found that the citronellal is the highest percentage (85.00%) followed by citronellol (4.75%), citronellyl propanoate (2.74%), delta-3-carene (1.15%), geranyl acetate (0.84%), (E)-ß-ocimene (0.69%), linalool (0.42%), terpinolene (0.40%), myrcene (0.35%), camphene (0.25%), ßpinene (0.24%), and a-Phellandrene is the lowest percentage (0.05%). 3-(4,5- dimethylthiazol- 2yl)-2,5-Diphenyl tetrazolium bromide (MTT) test was used to measure cytotoxicity of the oil and from this research it was found that the essential oil of C. hystrix (leaves) showed less toxic to the normal human liver cells (WRL 68) with the highest value of ICso (40.23±14.86 ug/mL) where it required a higher concentration of the C. hystrix (leaves) oil to inhibit the activity of the cells by 50% while the low dose concentration of paclitaxel reduced the percentage viable cells (0.0016±0.0003 ug/mL). There were 40 respondents participated this survey which were randomly assigned into two groups, control group (treated with virgin coconut oil (VCO) since this oil has no scent and it is typically used as a carrier oil) and the C. hystrix oil group and each group consists of 20 respondents. Visual analog scale (VAS) was used for this survey for the subjects to rate their emotional condition in order to assess subjective behavioural arousal in terms of relaxation, vigour, calmness, attentiveness, mood and alertness after inhalation. Data obtained in this study were analyzed using Mann-Whitney-U-Test, Wilcoxon Signed Rank Test, and Spearman's Rho Correlation. Based on the Mann-whitney U Test result, it showed that C. hystrix oil gave arousal effects in relaxation, vigorous and attentiveness and this data was supported by Wilcoxon signed rank test data for beginning and ending time where the data of C. hystrix oil category were significantly different in score of effects at the beginning and ending observation data for relaxation, vigorous and attentiveness rated by respondents. From this finding, C. hystrix oil gave arousal effects in relaxation, vigorous and attentiveness and these were supported by the Spearman's Rho Correlation test where relaxation had positive medium correlation with variable vigorous, r=0.47, n= 20, p<0.05, and variable vigorous had positive strong correlation with variable attentiveness, r=0.74, n= 20, p<0.05. The C. hystrix leaves oil has been experimentally shown to have a positive effect on relaxation, vigorous and attentiveness than subjects in the control group and these results provide evidence for its use in aromatherapy for the relief of depression and uplifting mood in humans and this might be due to higher content of citronellal in C. hystrix leaves oil and it is safe to be used. melegakan kemurungan dan menaikkan mood manusia dan ini mungkin disebabkan o%h kandungan citronellal yang tinggi di dalam daun minyak pati C. hystrix dan is selamat digunakan. vii